2021
DOI: 10.1155/2021/6657206
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract EGB761 Ameliorates the Extracellular Matrix Accumulation and Mesenchymal Transformation of Renal Tubules in Diabetic Kidney Disease by Inhibiting Endoplasmic Reticulum Stress

Abstract: The study is aimed at investigating the effects of Ginkgo biloba extract EGB761 on renal tubular damage and endoplasmic reticulum stress (ERS) in diabetic kidney disease (DKD). A total of 50 C57BL/6 N mice were randomly divided into the normal group, DKD group, DKD+EGB761 group (36 mg/kg), and DKD+4-phenylbutyrate (4-PBA) group (1 g/kg). The DKD model was replicated by high-fat diet combined with intraperitoneal injection of streptozotocin (STZ). Renal tubular epithelial cells (HK-2) were divided into the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“… 35 EMT is also one of the important causes of tubulointerstitial fibrosis in DKD, so EMT of renal tubular cells is considered to be a key process in the development of tubulointerstitial fibrosis in DKD. 36 By analyzing the expression of SMA, Ecad, and wound-healing assays, we found that EMT occurred in renal tubular epithelial cells in a high-glucose environment and recovered after metformin intervention. In addition, we found that the increase of VDR was accompanied by the down-regulation of EMT by calcitriol intervention.…”
Section: Discussionmentioning
confidence: 90%
“… 35 EMT is also one of the important causes of tubulointerstitial fibrosis in DKD, so EMT of renal tubular cells is considered to be a key process in the development of tubulointerstitial fibrosis in DKD. 36 By analyzing the expression of SMA, Ecad, and wound-healing assays, we found that EMT occurred in renal tubular epithelial cells in a high-glucose environment and recovered after metformin intervention. In addition, we found that the increase of VDR was accompanied by the down-regulation of EMT by calcitriol intervention.…”
Section: Discussionmentioning
confidence: 90%
“…Except for renal glucose metabolism, late renal changes of DKD mainly include renal tubular epithelial atrophy, collagen deposition, activation of myofibroblast and matrix, inflammatory cell influx, and epithelial-mesenchymal transition (EMT) ( 134 , 135 ). Studies showed that SIRT1 mainly regulated cell apoptosis induced by renal tubular oxidative stress ( 54 , 78 , 79 , 93 ), fibrosis ( 76 , 77 ) and EMT ( 77 , 93 ).…”
Section: Role Of the Sirtuin Family In Diabetic Kidney Diseasementioning
confidence: 99%
“…As ER stress inhibition has proved to ameliorate the fibrotic progression, it has been suggested that its blockade could be a new therapeutic approach for fibrosis [ 355 , 356 , 357 ]. One of the possible ways in which ER stress could lead to fibrosis is through fibroblast differentiation and collagen formation by TGF-β upregulation, as PERK and IRE1 activation have been seen to increase TGF-β expression [ 358 , 359 , 360 ].…”
Section: Mechanisms Involved In Fibrosis Progressionmentioning
confidence: 99%